PENGAWASAN PENEMPATAN REKLAME OLEH DINAS TATA RUANG DAN BANGUNAN DI KOTA PEKANBARU - Varyan Charestha Falerial; Ernawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Billboard is a means of information media used to deliver a message to another party. Billboards are used in order to promote a product to consumers. Both delivered orally visual, or a combination of both. By having a goal is that everyone knows that billaboard product. Placement of the billboard outside the room had a considerable influence on urban life for advertisement media often have orientation on the location of the main streets of urban which has the advantage of strategic location, easily accessible, and readiness so that the information can be delivered effectively.Advertisement itself visually to have a major contribution to the impression of an environment. Besides the contribution given to the government is an admission of retribution advertisement revenue (PAD). So that in practice more often concerned with retribution than the beauty of the city, security and environmental safety.The concept of the theory used is the theory of supervision by Manullang (2008: 185). The indicators in this research resources, supervision, facilities and infrastructure. Key informants of this study is Head of Department Spatial Planning and Building Pekanbaru, Head of Civil Service Police Unit of Pekanbaru. To complement the informant is a staff department of Spatial Planning and Building Pekanbaru, staff Administrative Civil Service Police Unit Pekanbaru and billboard owners. This research is a qualitative descriptive study using data collection techniques with a bunch of observation and interviews obtained from the research informants.Based on the research that has been done, based on the data analysis process it has been known that the demolition of billboards in the city of Pekanbaru run poorly or less than optimal. Poor or sub-optimal. Less good or less optimal control of billboards in the city of Pekanbaru because it is influenced by many things, whether it be a barrier effect of the enforcement rules themselves, from the owner of the billboard and the community. A factor that is affecting is the communication and coordination between the parties the service itself.Keywords : Monitoring, Control, Billboards